Analysis of Limited Liability Company Establishment Procedures PT. Annajwa Islamic Tour & Travel on Jln. Medan City Red Market - Sabda Dian Nurani Siahaan; Annisa Az Zahra; Riziroh Wiam; Desi Panjaitan; Tri Nazwa Nafira (Asian Journal of Applied Business and Management, 2023)
This journal aims to analyze the procedures for establishing a Limited Liability Company (PT) Annajwa Islamic Tour & Travel on Jln. Pasar Merah, Medan City. This study aims to understand the steps that must be taken in the establishment of PT. Annajwa Islamic Tour & Travel. The research method used is descriptive qualitative. The results of the research show that the procedure for establishing PT. Annajwa Islamic Tour & Travel at Jln. Pasar Merah, Medan City requires fulfilling administrative requirements, licensing, and submitting documents. Establishment procedures (PT) and effective cooperation with the authorities are important to expedite the establishment of PT in Medan City.